Progesterone Receptor A (PR(A)) and PR(B)-Independent Effects of Progesterone on Gonadotropin-Releasing Hormone Release - Sleiter, Nicole (The Endocrine Society, 2009)
Progesterone’s (P4) negative feedback actions in the female reproductive axis are exerted in part by suppression of hypothalamic GnRH release. Here we show that P4 can inhibit GnRH release by a mechanism independent of a nuclear P4 receptor (PR(A/B)). Injections of P4, but not vehicle, allopregnanolone, or dexamethasone, acutely suppressed LH levels in both wild-type and P4 receptor knockout ovariectomized mice; pituitary responsiveness to GnRH was retained during P4 treatment, indicating a hypothalamic action. Superfusion of GnRH-producing GT1-7 cells with medium containing 10(−7) m P4 produced a rapid reduction in GnRH release. Incubation with P4 (10(−9) to 10(−7) m) inhibited forskolin-stimulated cAMP accumulation; cotreatment with pertussis toxin prevented this effect. Treatment of GT1-7 cell membranes with P4 caused activation of an inhibitory G protein (G(i)), as shown by immunoprecipitation with a G(i) antibody of most of the increase in membrane-bound [(35)S]GTPγ-S. Saturation binding analyses demonstrated the presence of a high affinity (K(d) 5.85 nm), limited capacity (Bmax 62.2 nm) binding site for P4. RT-PCR analysis revealed the presence of mRNAs encoding both isoforms of the membrane P4 receptors, mPRα and mPRβ. Western blotting, immunocytochemistry, and flow cytometry experiments similarly revealed expression of mPR proteins in the plasma membranes of GT1-7 cells. Treatment with mPRα siRNA attenuated specific P4 binding to GT1-7 cell membranes and reversed the P4 inhibition of cAMP accumulation. Taken together, our results suggest that negative feedback actions of P4 include rapid PR(A/B)-independent effects on GnRH release that may in part be mediated by mPRs.